THE ROLE OF INTESTINAL TRANSLOCATION IN THE ORIGIN OF ENDOTOXEMIA IN ACUTE POISONING AND DETOXIFICATION EFFECT OF INTESTINAL LAVAGE - V. A. Matkevich; E. A. Luzhnikov; M. V. Belova; N. V. Yevdokimova; E. D. Syromyatnikova; Yu. A. Kurilkin (Неотложная медицинская помощь)
BACKGROUND. Endogenous intoxication (EI), following acute poisoning, aggravates the disease course, increases the risk of complications and death, as well as the scope and duration of therapeutic measures. That is why, prevention and correction of EI in acute poisoning with psychopharmacological drugs (PPD) as well is relevant.MATERIAL AND METHODS. In 115 patients with PPD poisoning, intestinal lavage (IL) was performed, 50 patients were control group. EI was evaluated by the level of medium molecular weight peptides (MMWP) and lipopolysaccharides (LS) in serum, albumin tests, leukocyte index of intoxication (LII) and shear index of neutrophils (SIN). The level of MMWP in blood and intestinal lavage fluid (intestinate) in 23 patients and 22 healthy donors was measured.RESULTS. Initial level of WWMP in the blood of patients exceeded the norm by 32%, LS — by 10 times, LII — by 6.3 times and SIN — by 2.4 times. At the beginning of the gastrointestinal lavage, the intestinate’s MMWP in patients and donors exceed their values in the blood. At the end of the IL it fell by 3– 6 times. This was accompanied by a fall of MMWP in blood of patients by 18.2%, LS — 50%, and LII and SIN by 52% and 70% respectively. In the comparison group LII and SIN continued to grow during the 1st day.CONCLUSION. In patients with uncomplicated poisoning with PPD the source of endotoxemia was the intestines. The IL promotes the elimination of endogenous toxins and the reduction of EI.